'An outward sign of an inward grace': how African diaspora religious identities shape their understandings of and engagement in international development. Issue 6 (2nd November 2021) - Ademolu, Edward
ABSTRACT: Mainstream development discourse and practice often marginalise the significance of 'religion' and 'faith' for international development and humanitarianism. However, recent geopolitical events have prompted attitudinal and epistemological developments, with religion and faith considered an almost obligatory agenda for development scholarship. Despite current celebrations, scant attention is paid to the paramount role of religion for faith-based development actors such as African diaspora individuals and communities. Using focus group discussions, this article examines how the religious-faith identities of UK Nigerians specifically, shape their meanings for and engagement in international development. I reveal that Nigerian remittances and non-monetary contributions and services to their heritage country are constituted within moral (and cultural) obligations, justifications and values that are distinctly 'religious'. So too, that Nigerians largely construe international development as a demonstrable 'practice' of their faith-based identities. Consequently, I call for a (re)theorisation of development to subsume transnational Afro-religious diasporic performativity. While focused on Nigerians, these findings are nonetheless relevant for wider UK-based African diaspora.